Pertimbangan Teknis Pertanahan sebagai Instrumen Pengendalian Pemanfaatan Ruang di Kantor Pertanahan Kabupaten Mamuju - Amran AS Wahidin; Sutaryono Sutaryono; Rakhmat Riyadi (Sekolah Tinggi Pertanahan Nasional, 2019)
Abstract: Implementation of spatial utilization control activities in Mamuju Regency, West Sulawesi Province, is not running optimally because the Regional Regulation on Regional Spatial Planning (Perda RTRW) of Mamuju Regency has not been issued. This regulation vacuum has a great impact in the service of the application for the granting of a location permit and change permit for land use, especially in terms of fulfilling the permit requirements in the form of an application of land technical considerations carried out by the Land Office of Mamuju Regency, while the Land Technical Consideration Service which contains technical studies of land stewardship and availability the land must be in accordance with the Spatial Plan of the territory. Phase The activities of land technical considerations at the Land Office of Mamuju Regency are carried out in accordance with the Cash No. 2 of 2011, in addition to its implementation in accordance with spatial planning, the Land Office added a recommendation letter from the Public Works and Spatial Planning office, the Agriculture Service and the Plantation Service in the attachment to the application requirements. The Role of Land Technical Considerations as an Instrument for Spatial Utilization in Mamuju Regency, namely Land Technical Consideration is the main requirement in obtaining a Permit for Land Use Change and Location Permit, this is because in the Minutes of Land Technical Consideration there is a technical study on Land Stewardship and Technical Assessment of Land Availability. Keywords: control, space utilization, land technical considerations Intisari: Kekosongan Regulasi Rencana Tata Ruang Wilayah (Perda RTRW) Kabupaten Mamuju berdampak dalam pelayanan permohonan pemberian Izin Lokasi dan Izin Perubahan Penggunaan tanah. Tujuan penelitian ini dilakukan untuk megetahui pelaksanan dan peran pertimbangan teknis pertanahan dalam ijin lokasi dan ijin perubahan penggunaan tanah, Penelitian ini dilaksanakan dengan menggunakan Metode Kulitatif dengan Pendekatan Deskriptif. Hasil penelitian menunjukan dalam pelaksanaannya telah sesuai dengan aturan Peraturan Kepala Badan Pertanahan Nasional No. 2 Tahun 2011 tentang Pedoman Pertimbangan Teknis Pertanahan dalam Penerbitan Izin Lokasi, Penetapan Lokasi dan Izin Perubahan Penggunan Tanah. Peran Pertimbangan Teknis Pertanahan sebagai Intrumen Pengendalian pemanfaatan ruang di Kabupaten Mamuju merupakan syarat utama, didalam mendapatkan Izin Perubahan Penggunaan Tanah dan Izin Lokasi. Saran seharusnya yang menjadi dasar dalam pemberian Izin Perubahan Penggunaan tanah berupa Surat Keputusan. Pemerintah Daerah Kabupaten Mamuju segera mensahkan Peraturan Daerah Tentang Rencana Tata Ruang Wilayah Kabupaten Mamuju Kata Kunci : pengendalian, pemanfaatan ruang, pertimbangan teknis pertanahan